PENGARUH KOMPOSISI MEDIA TANAM DAN KONSENTRASI PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) TERHADAP PERTUMBUHAN DAN HASIL CABAI RAWIT (Capsicum frutescens L.) - Imanda Setyawan; Juli Santoso; Saefurrohman (Postgraduate, University of Mataram, 2025)
Chili pepper (Capsicum frutescens L.) is a high-value horticultural commodity, but its productivity is often hampered by the excessive use of chemical fertilizers. This study aims to evaluate the effect of planting medium composition and plant growth-promoting rhizobacteria (PGPR) concentration on the growth and yield of chili pepper. The study was conducted from May to August 2025 at the Kedungrejo Seed Garden, Madiun Regency, using a factorial Randomized Block Design (RAK) with two factors: planting medium (soil, soil + compost, soil + manure, and soil + compost + manure) and PGPR concentration (0, 8, 16, and 24 ml/L), each replicated three times. Significant interactions were found between planting medium and PGPR on plant height, number of leaves, and fruit weight. The combination of soil + manure with PGPR at doses of 8 and 16 ml/L produced the highest values ​​for fruit weight (up to 2.99 g) and number of leaves (44). Soil and manure alone also increased root weight and fruit number while accelerating flowering. PGPR at a dose of 16 ml/L significantly increased shoot dry weight and shortened the harvest period. This study demonstrates that combining organic media with PGPR can sustainably increase chili productivity.